Killing Reagan : the violent assault that changed a presidency - O'Reilly, Bill; Dugard, Martin (New York : Henry Holt and Company, 2015)
Just two months into his presidency, Ronald Reagan lay near death after a gunman's bullet came within inches of his heart. His recovery was nothing short of remarkable -- or so it seemed. But Reagan was grievously injured, forcing him to encounter a challenge that few men ever face. Could he silently overcome his traumatic experience while at the same time carrying out the duties of the most powerful man in the world? Killing Reagan reaches back to the golden days of Hollywood, where Reagan found both fame and heartbreak, up through the years in the California governor's mansion, and finally to the White House, where he presided over boom years and the fall of the Iron Curtain. But it was John Hinckley Jr.'s attack on him that precipitated President Reagan's most heroic actions.
Includes bibliographical references and index.
Keywords: Reagan, Ronald -- Assassination attempt, 1981.; United States -- Politics and government -- 1981-1989.